2015
DOI: 10.3389/fncir.2014.00151
|View full text |Cite
|
Sign up to set email alerts
|

The role of the serotonergic system in locomotor recovery after spinal cord injury

Abstract: Serotonin (5-HT), a monoamine neurotransmitter synthesized in various populations of brainstem neurons, plays an important role in modulating the activity of spinal networks involved in vertebrate locomotion. Following spinal cord injury (SCI) there is a disruption of descending serotonergic projections to spinal motor areas, which results in a subsequent depletion in 5-HT, the dysregulation of 5-HT transporters as well as the elevated expression, super-sensitivity and/or constitutive auto-activation of specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 159 publications
(208 reference statements)
4
88
0
4
Order By: Relevance
“…4D). Although we cannot currently distinguish whether increased numbers of 5‐HT serotonergic fibers in anti‐HMGB1 mAb treatment groups were attributable to the retention of pre‐existing fibers or to newly sprouted fibers after injury, these data suggest that anti‐HMGB1 mAb treatment led to an increase in 5‐HT‐positive fibers in the spinal cord after injury, resulting in functional recovery as was observed in previous studies .…”
Section: Resultsmentioning
confidence: 53%
“…4D). Although we cannot currently distinguish whether increased numbers of 5‐HT serotonergic fibers in anti‐HMGB1 mAb treatment groups were attributable to the retention of pre‐existing fibers or to newly sprouted fibers after injury, these data suggest that anti‐HMGB1 mAb treatment led to an increase in 5‐HT‐positive fibers in the spinal cord after injury, resulting in functional recovery as was observed in previous studies .…”
Section: Resultsmentioning
confidence: 53%
“…More important, both our results of BMS score and other report were consistent with this change. Ghosh M in turn confirmed this view, following SCI, there was a disruption of descending serotonergic projections to spinal motor areas, which resulted in a subsequent depletion in 5-HT [36]. These demonstrated that 5-HT played an important role in modulating the activity of spinal networks involved in vertebrate locomotion.…”
Section: Akt Pathway Activated By Bdnf Overexpression May Relate To Tmentioning
confidence: 55%
“…The raphespinal axon is the main nerve fibre mediating locomotor function in the spinal cord (Ghosh & Pearse, ). Serotonin (5‐HT) is a neurotransmitter specifically transmitted by raphespinal axons in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%